The Literary and philosophical conceptions of Laza Kostić - Aleksić, Slađana V. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
Laza Kostić, in the early seventies of the XIX century, opposed the utilitarianism of Nikolay Chernyshevsky and Svetozar Marković, and advocated the idea of aestheticism in poetry and art. In his study about Jovan Jovanović Zmaj, Kostić had discovered two opposing processes in the poet, which he symbolically named the battle between the dragon and the nightingale. Kostić’s conception about the origin of poetry is at the intersection of romanticist poetics about creation from divine inspiration, and a philosophical concept of the interference as a basic principle. The paper sheds light on the correspondence among the philosophical and literary views of Lazа Kostić and his artistic work.